Comparación de las características mecánicas de un diseño Marshall, los módulos de resiliencia de una mezcla asfáltica de rodadura convencional y una mezcla de grano caucho (2022)
The following research is carried out on two different types of asphalt mixtures, the first one is a type of mixture called MCCs 19, better known as GCR, since it contains recycled rubber grain and on the other hand a mixture of type MD12, to which its name is attributed by its granulometry, in which its largest particles should not exceed 12.5mm.